A felicidade propagada : publicidade, história e imaginário de consumo em Passo Fundo-RS - Dalbosco, Cleber Nelson (2008)
Making use of advertisements run in the local newspaper O Nacional, figuring the ending of 60 s and beggining of 70 s, this work intended to indicate some characteristics related to the context of the Passo Fundo society, trying to understand the effectived relationship by advertising seduction. Identifying events, the period in which they were prepared and served at the same time that empower the understanding of concepts daydreamed by individuals as "comfort", "modernity", preservation of economic and financial resources